Abnormal leukotriene C4 released by unaffected jejunal mucosa in patients with inactive Crohn's disease. Issue 4 (April 1994) - Casellas, F; Guarner, F; Antolín, M; Rodríguez, R; Salas, A; Malagelada, J R
Abstract : The mucosal release of inflammatory mediators is enhanced in active inflammatory bowel disease. This study examines whether leukotriene C4 production occurs in apparently unaffected segments of the gut. The intraluminal release of leukotriene C4 was determined by jejunal perfusion in seven healthy controls, in nine patients with chronic ulcerative colitis, and in 13 patients with Crohn's disease (six with ileal disease, and seven with only colonic). All patients were in clinical remission and none of them had evidence of jejunal involvement. Mild intraluminal irritation with a 2.5 mmol/l deoxycholic acid solution was induced to stimulate local inflammatory mechanisms. The release of DNA (a marker of mucosal desquamation) and prostaglandin E2 (PGE2) was simultaneously measured. Jejunal release of DNA was higher in Crohn's disease patients than in ulcerative colitis or healthy controls. Basal release of PGE2 was similar in the three groups of patients. Basal release of leukotriene C4 was considerably enhanced, however, in Crohn's disease patients compared with healthy controls. In ulcerative colitis patients, basal leukotriene C4 release was non-significantly different from controls. Bile acid perfusion stimulated PGE2, leukotriene C4, and DNA release in all groups studied, but leukotriene C4 release was significantly higher in Crohn's disease patients. It is concluded that in inactive Crohn's disease there is an enhanced intraluminal release of leukotriene C4 in apparently unaffected segments of proximal small bowel, which may reflect fundamental changes in the function of the gut mucosal barrier.